Crowning his innocent assistant - Adams, Millie (Adams, Millie. The Kings of California, 2021)
"Countless women would be thrilled to marry King Matteo de la Cruz. Yet his brilliant personal assistant, Livia, flat-out refuses his proposal- and then quits! Matteo is outraged, then intrigued. Can anything make his ideal queen reconsider? Livia has loved Matteo since he plucked her from the gutter as a teenager. Wearing his crown yet not having his heart would be unbearable. Still, their mind-blowing kiss makes innocent Livia long for his touch. If she surrenders to their desire just once, will she be able to say goodbye for good?" --